2020
DOI: 10.1017/s0954422419000283
|View full text |Cite
|
Sign up to set email alerts
|

Expert consensus on low-calorie sweeteners: facts, research gaps and suggested actions

Abstract: A consensus workshop on low-calorie sweeteners (LCS) was held in November 2018 where seventeen experts (the panel) discussed three themes identified as key to the science and policy of LCS: (1) weight management and glucose control; (2) consumption, safety and perception; (3) nutrition policy. The aims were to identify the reliable facts on LCS, suggest research gaps and propose future actions. The panel agreed that the safety of LCS is demonstrated by a substantial body of evidence reviewed by regulatory expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
63
0
25

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(96 citation statements)
references
References 44 publications
2
63
0
25
Order By: Relevance
“…Further development of such markers and better linkage of food composition and dietary databases are therefore needed to help monitor changing use and consumption (Ashwell et al . 2020).…”
Section: Low‐calorie Sweeteners – An Easy Solution To Reformulation?mentioning
confidence: 99%
See 1 more Smart Citation
“…Further development of such markers and better linkage of food composition and dietary databases are therefore needed to help monitor changing use and consumption (Ashwell et al . 2020).…”
Section: Low‐calorie Sweeteners – An Easy Solution To Reformulation?mentioning
confidence: 99%
“…More recent statements have concluded that replacing free sugars with LCS may help to reduce energy intake and assist with weight management (BDA 2016; Diabetes UK 2018; Ashwell et al . 2020). This strategy may be especially useful for those who are accustomed to sugar‐sweetened products (Gardner et al .…”
Section: Low‐calorie Sweeteners – An Easy Solution To Reformulation?mentioning
confidence: 99%
“…allgemein Personen mit Diabetes und basiert auf den Empfehlungen einer ausgewogenen Ernährung: Auch wenn ein isokalorischer Austausch Saccharose-oder Fruktose-haltiger Lebensmittel durch andere Kohlenhydrate ähnliche Effekte auf den Blutglukosespiegel oder andere metabolische Parameter haben mag, sollte der Verzehr zugunsten von Lebensmitteln mit einer höheren Nährstoffdichte minimiert werden [54] und die ausgewählten Kohlenhydrat-haltigen Lebensmittel in der Ernährung sollten idealerweise reich an Ballaststoffen, Vitaminen, Mineralien sein und arm an zugesetzten Zuckern, Fetten und Natrium [55]. [62,63].…”
Section: Wissenschaf Tlicher Hintergrundunclassified
“…Einige Beobachtungsstudien zeigen einen positiven Zusammenhang zwischen dem Verzehr von Süßstoffen und dem Risiko für Typ-2-Diabetes und anderen kardiometabolischen Erkrankungen; eine Verzerrung der Studienergebnisse durch Übergewicht und reverse Kausalität stellt dabei jedoch häufig ein Problem dar [61,63,64].…”
Section: Wissenschaf Tlicher Hintergrundunclassified
See 1 more Smart Citation